DNA and mRNA sequence of the immune protective DNA Iigase I gene match the rev response element of HIV - Dandekar, Thomas; Dandekar, Gudrun (DNA sequence, 1996)
A motif search for DNA and mRNA sequences matching the rev response core element of HIV identified only DNA ligase I to display the element both in DNA and mRNA and to have phylo-genetic conservation of it. Genetic impairment of DNA ligase I is already known to lead to severe immunodeficiency in man. A similar impairment may result from HIV rev protein binding to the DNA ligase I mRNA.
Elektronische Reproduktion der Druck-Ausgabe 11. Juli 2009
Gesehen am 08.08.2024